Optimization of toolpath trajectories on arbitrary surfaces - Gaspar, Miguel (2015)
Given an arbitrary region on the plane, modelled as a graph with a symmetry, we describe a procedure to find the best orientation for slicing, via a zigzag tool-path trajectory based curve, in order to minimize its discontinuities. We also develop some directions on how to generalize the procedure up to the level of optimizing tool-path trajectories on arbitrary surfaces rather than planar regions only.